Pengembangan Modul Bahasa Indonesia Berbasis Karakter Bangsa di STMIK Stikom Bali - Ni Putu Desy Damayanthi (STKIP Suar Bangli, 2019)
This study aims to develop Indonesian language modules combined with national character. The backgroundof this research is that each course must instill character values in each learning material, including Indonesianlanguage courses. This research aims to produce valid, practical, and effective Indonesian language teaching materialsthat can be implemented to students especially Indonesian language courses. The study was divided into four stepscalled four-D (1) define; (2) design; (3) developing; and (4) spread. However, the duration of the study was only eightmonths, so that the study was only able to reach the third level (to develop). The product of this research is a nationcharacter language module that is ready for use by Indonesian language lecturers. The research objects wereIndonesian students and lecturers at STMIK Stikom Bali. Data collection techniques used in this study werequestionnaire techniques, interview techniques and test techniques. While the data analysis technique uses descriptivequalitative analysis techniques and descriptive statistical analysis techniques. Based on the results of the analysis it canbe concluded that the Indonesian language module based on the nation's character that is developed is suitable to beused and implemented by students, especially in Indonesian language courses.